Analysis of the Effects of Direct Payment Subsidies for Environmentally-Friendly Agriculture on Income of Rice Farmers in Shiga, Japan - Katrina Santos, Danielle; Shimada, Koji (European Journal of Sustainable Development, 2019)
This study will determine the economic effects of direct payment subsidies for Environmentally-Friendly Agriculture on income of rice farmers in Shiga Prefecture, Japan. It will specifically aim to: (1) analyze the effect of reduced chemical and fertilizer use on income and (2) come up with policy recommendation related to the implementation of direct payment subsidy. Environmentally-friendly agriculture has been promoted for over two decades as a response to the environmental challenges brought by climate change and biological loss. The Japanese government has endeavored to seek appropriate policies which reflect various environmentally-friendly farming practices such as organic farming and reduction of chemicals and fertilizers. The agro-environmental policy in Shiga is one of the earliest and most advanced in Japan. It aims to promote environmentally-friendly agriculture among farmers and to engage various stakeholders to protect the environment using the “Kodawari” slogan for Lake Biwa conservation and eco-farming. Rice as a staple food in Japan, this study will seek to address the notion that output and income of rice farmers receiving direct payment subsidies for agricultural inputs has not increased as evidenced by the study conducted by Kim (2014). In addition, chemical input is higher in Japan than most developed countries, this study will also aim to disprove the findings from the study conducted by Masuda (2016) that the current level of direct payment subsidy has only resulted to economic disadvantages in output for smaller environmental advantages. This study will contribute to the literature by analyzing an unexplored mandate of the direct payment scheme, particularly on the reduced use of chemicals and fertilizers, by explicitly determining the economic effects of the said program on income to determine how the gains from environmentally-friendly agriculture influence farmer’s decision to produce. Keywords: rice, direct payment subsidy, environmentally-friendly agriculture, income.